Boosting Ethylene/Ethane Separation within Copper(I)‐Chelated Metal–Organic Frameworks through Tailor‐Made Aperture and Specific π‐Complexation - Zhang, Ling (Adv Sci (Weinh), 2019)
The development of new materials for separating ethylene (C(2)H(4)) from ethane (C(2)H(6)) by adsorption is of great importance in the petrochemical industry, but remains very challenging owing to their close molecular sizes and physical properties. Using isoreticular chemistry in metal–organic frameworks (MOFs) enables the precise design and construction of target materials with suitable aperture sizes and functional sites for gas separations. Herein, it is described that fine‐tuning of pore size and π‐complexation simultaneously in microporous copper(I)‐chelated MOFs can remarkably boost the C(2)H(4)/C(2)H(6) adsorption selectivity. The judicious choice of organic linkers with a different number of carboxyl groups in the UiO‐66 framework not only allows the fine tuning of the pore size but also immobilizes copper(I) ions onto the framework. The tailor‐made adsorbent, Cu(I)@UiO‐66‐(COOH)(2), thus possesses the optimal pore window size and chelated Cu(I) ions to form π‐complexation with C(2)H(4) molecules. It can rapidly adsorb C(2)H(4) driven by the strong π‐complexation interactions, while effectively reducing C(2)H(6) uptake due to the selective size‐sieving. Therefore, this material exhibits an ultrahigh C(2)H(4)/C(2)H(6) selectivity (80.8), outperforming most previously described benchmark materials. The exceptional separation performance of Cu(I)@UiO‐66‐(COOH)(2) is validated by breakthrough experiments for 50/50 v/v C(2)H(4)/C(2)H(6) mixtures under ambient conditions.